Countering The Erosion of Pancasila Values in The Millennial Generation Through a Digital Approach - Rahmat Salam; Evi Satispi; Izzatussolekha Izzatussolekha; Muhammad Sahrul (International Journal of Artificial Intelligence Research, 2022)
In the era of globalization, western culture has established itself in Indonesia. It has become a common occurrence and has had a profound impact on the lives of the Indonesian people, particularly the millennial generation, which should be the nation's next generation. Internet-based inculcation of the Pancasila ideology's values is vitally important in the digital age. All Indonesians, even the millennial age, may comprehend and implement the Pancasila ideals in the life of society, nation, and state if they are taught the necessary formulas and procedures. This study employs a qualitative, descriptive methodology. The results demonstrate that Pancasila, as a philosophy, may be stated in a variety of basic living forms. As an open worldview, Pancasila cannot be divorced from the impact of contemporary societal values. The growth of fake news, such as social politics and racial hatred, is currently putting Pancasila to the test. As a result, as members of the millennial generation born during the digital era, they must be proficient with technology and social media. In addition, social media platforms offer opportunity for millennials to adopt Pancasila values. By sticking to the significance of Pancasila, the state's position is secured and national integration is maintained